Implementing ARCS model to design a motivating multimedia e-book for polytechnic ESL classroom - Annamalai, Subashini (Universiti Teknikal Malaysia Melaka, 2016)
This paper describes the design of multimedia E-book (mE-book) based on the Keller’s ARCS Model of Motivational Design (1987).This paper also presented the implementation of mE-book as a motivating learning aid to promote ESL language learning in Polytechnic classrooms. Sixty (60) Polytechnic students experienced mE-book in their language classroom and their perceived motivation towards this learning material is measured using the Instructional Materials Motivation Survey (IMMS). This study is an attempt to adduce a scope for implementing multimedia in language learning in a motivating way for adult learners.